Handicaps et contradictions du Programme de villes nouvelles au Maroc - Tarik Harroud (Les Cahiers d’EMAM)
An immense program of new towns was announced in 2004 by the Department of the Housing environment and the Town planning with as ambition to ease congestion in big cities and to reduce the considerable deficit in social housing. After eight years of its begening, it seems that the realizations are clearly lower compared with the ambitions in the point to arouse lively reactions on behalf of the political, economic and associative authorities. The analysis of the process of its implementation, focused on the example of Tamesna, allowed to rerelease the diverse technical and legal obstacles having marked its realization but also a set of contradictions which are revealing of a crisis of governance in the management of this public strategy. In spite of this numerous obstacles, it is to underline the stubbornness of the Department to continue the program with the announcement of creation of new operations.